Modified Delphi Technique in Analysing Contents of Green Skills Module for Design and Technology Subject - Alwi, Amarumi; Kamis, Arasinah; Moreno Herrera, Lazaro; Luis Yturria Motenegro, Pedro; Mat Nashir, Irdayanti; Che Kob, Che Ghani; Tze Kiong, Tee (Journal of Technical Education and Training, 2019)
The Green Skills Module (GS) is a teaching module of the Design and Technology (DT) subjects developed to introduce green skills and foster a positive attitude towards the environment. This article is intended to obtain the consensus of a panel of experts on the content analysis of the GS module. Modified Delphi Technique was used to analyse the contents of the GS Modules. Nine experts in the curriculum, Technical Vocational Education and Training (TVET), Environmental Education as well as DT excellent teachers were selected through the method of purposive sampling. The data were collected using a semi-structural interview method for the first round and questionnaires for the second round. Based on the findings, two elements, namely knowledge and practice of green skills included in the GS module, are analysed using IBM SPSS version 21 to get the value of ‘Inter Quartile Range’ (IQR) and the Wilcoxon Test. The findings show that all the items for practice have been agreed upon by the experts while two items of knowledge have been rejected. This study indicates that the application of Modified Delphi Technique can be a new alternative method in analysing programme content in the development of a module.